A Discourse-Stylistic analysis of Harold Pinter’s Victoria Station: Simpson’s Three Ss Model as a Sample - Maroufi, Soumia (My University, 2017)
Abstract The general purpose of the present work is to demonstrate the way in which discourse analysis can be useful in the stylistic analysis of dramatic texts mainly that of Harold Pinter‟s absurdist texts .This work aims at isolating the linguistic patterns that typify Pinter‟s writings and explain the way he fashions language to create absurdist themes and motifs. The work is an application of Paul Simpson‟s model to Pinter‟s play Victoria Station to demonstrate the way this method of analysis, which draws on other areas of linguistics mainly pragmatics and discourse analysis, can account for the absurd nature of Pinter‟s dialogue. This model explores three different aspects of language use: structure, strategy and setting. The work, then, seeks to analyse how and why Pinter‟s characters in Victoria Station employ certain linguistic patterns at specific contexts to generate particular dramatic effects. Moreover, this work illustrates that the violation of the conversational rules is the source of absurdity. It shows that what critics call inefficient interactions in Pinter‟s plays is actually the way Pinter fashions language to generate particular dramatic effects whereby he builds particular language patterns to convey messages about his characters and his plays as well. Further, this works engages in up-to-date reading of Camus‟s philosophy of the absurd as articulated by Michael.Y. Bennett to demonstrate that Pinter‟s Victoria Station not only means on a more general level but it is also not so about the meaninglessness of life as it is about how to make life meaningful.---------------------------------------------------------------------------------------------------------------------------Résumé:Le but général du travail présent est de démontrer la façon dont l'analyse du discours peut être utile dans l'analyse stylistique des textes du théâtre du genre absurde principalement ceux d‟Harold Pinter. Ce travail vise à isoler les caractères linguistiques qui caractérisent les textes de Pinter et à expliquer la manière dont il façonne la langue pour créer des thèmes absurdes .Le travail est une application du modèle de Paul Simpson à la pièce Victoria Station de Pinter pour démontrer comment cette méthode d'analyse, qui est basée sur plusieurs domaines de linguistique notamment la pragmatique et l'analyse du discours, peut dévoiler la nature absurde du dialogue de Pinter. Ce modèle explore trois aspects différents d'utilisation de langue : structure, stratégie et contexte. Le travail, alors, cherche à analyser comment et pourquoi les personnages de Pinter dans Victoria Station emploient certains caractère linguistiques dans des contextes spécifiques pour produire des effets dramatiques particuliers. De plus, ce travail à pour but d‟illustrer que la violation des règles conversationnelles est la source d'absurdité et de montrer ce que les critiques appellent interaction inefficace ou échec de communication dans les dialogues de Pinter est en fait délibérément conçu de cette manière par le dramaturge par lequel il construit des caractères linguistiques particuliers pour transmettre des messages sur ses personnages et ainsi que de ses pièces.------------------------------------------------------------------------------------------------------------ الملخص يحاول البحث إظهار أهمية تحليل الخطاب في تحليل النصوص الدسرحية مركزّا صاحبو على نموذج الكاتب الدسرحي العبثي ىارولد بنتر؛ ذلك أنّ جلّ كتابات ىارولد قد امتازت بالجانب اللغوي الذي كان يعكس في الغالب كل ما لو علاقة بالعبث. غير أنّ البحث حاول أن يعتمد على بيان نموذج بول سيمبسون الدطبّق أساسا على مسرحية ىارولد بنتر فيكتوريا ستايشن، بحكم أنّو يتماشى مع طبيعة الحقول اللغوية لاسيّما البراغماتية وتحليل الخطاب. ولتجسيد معالم تحليل الخطاب في إطاره الأسلوبي الذي امتازت بو كتابات ىارولد بنتر اعتمدنا على نموذج سيمبسون في تحليل النصوص وفق ثلاثة إجراءات وىي: السياق والاستراتيجية وأخيرا البنية اللغوية؛ ىذه الإجراءات الثلاث كانت سببا في إظهار كيف ولداذا استخدم ىارولد بنتر الأساليب اللغوية في سياقات لزدّدة من أجل بثّ إثارة معينة لدى الدتلقي. مثل ىذا النوع من الأساليب اللغوية التي امتاز بها ىارولد بنتر حاولت أن تعكس لنا أمرا آخر يتعلق بطبيعة وخصوصية الاستعمال؛ إذ الغالب في الخطاب العبثي لذارولد كان يمثل خروجا وانتهاكا لقواعد التخاطب الدتفق عليها عن طريق ما يسمى في لرال الأسلوبية بالانزياح أو الخروج عن الدألوف. من ىذا الدنطلق كل ما قيل في شأن أسلوب ىارولد من وصفو بعدم التواصل في جلّ حواراتو، ىو في الأصل يعكس رسائل وحقائق معينة اعتمدىا ىارولد قصدا وتعمدا للفت انتباه القارئ أو الدتلقي إلى ما احتوتو الشخصيات داخل الدسرحية من جهة، وإلى الإطار العام حول الدسرحية في حاللغة العربيةدّ ذاتها.